Strength training in female climacteric: Evidence and benefits according to scientific literature (Research, Society and Development, 2025)
Climacteric corresponds to the biological transition period that precedes and follows menopause, characterized by significant hormonal changes that impact women’s physical, metabolic, and emotional health. This phase, usually experienced between the ages of 40 and 65, is associated with symptoms such as sudden hot flashes, sleep disturbances, weight gain, loss of muscle mass and strength, as well as increased risk for cardiovascular disease and osteoporosis. Women in the climacteric period undergo a life transition that marks the end of reproductive capacity. During this phase, hormonal changes have significant impacts. In this context, physical exercise plays a central role, with Strength Training (ST), also known as resistance training or weight training, standing out. The present study aims to verify, through a literature review, the possible benefits of strength training for women in the climacteric period in terms of physical health, climacteric symptoms, and quality of life. To this end, the study seeks to: 1- Identify the effects of strength training on muscle strength and body composition. 2- Assess the impact of resistance exercise on bone mineral density and the prevention of sarcopenia. 3- Investigate the influence of training on climacteric symptoms (hot flashes, sleep disturbances, and mood changes). 4- Verify the effects on quality of life and psychological well-being.